1997
DOI: 10.1021/je960299u
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Aqueous Solubility of Selected Chlorobenzenes, Polychlorinated Biphenyls, and Dibenzofuran

Abstract: The aqueous solubilities of seven chlorobenzenes (1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,3,5trichlorobenzene, 1,2,3,5-tetrachlorobenzene, 1,2,4,5-tetrachlorobenzene, pentachlorobenzene, and hexachlorobenzene), five polychlorinated biphenyls (4-chlorobiphenyl, 4,4′-dichlorobiphenyl, 2,4,5-trichlorobiphenyl, 2,3,4,5-tetrachlorobiphenyl, and 2,2′,4,4′,6,6′-hexachlorobiphenyl), and dibenzofuran are reported over the range 5 to 45 °C, from which enthalpies of solution are deduced. The octanol-water partitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
1
45
1
Order By: Relevance
“…Combined with the solubility value cited in Table 1 this leads to DG f (aq) = -118. 41 and DG s = -16.31 kcal/mol, with an uncertainty of about 2 kcal/mol. This is in good agreement with the value in the Table. The value for cyanuric acid was challenged because sublimation might be accompanied by decomposition.…”
Section: Results Returned To Participantsmentioning
confidence: 96%
“…Combined with the solubility value cited in Table 1 this leads to DG f (aq) = -118. 41 and DG s = -16.31 kcal/mol, with an uncertainty of about 2 kcal/mol. This is in good agreement with the value in the Table. The value for cyanuric acid was challenged because sublimation might be accompanied by decomposition.…”
Section: Results Returned To Participantsmentioning
confidence: 96%
“…This could also be linked to the octanol-water partition coefficient, known to influence the adhesion of herbicides to cell surface (adsorption) and uptake or penetration of herbicides into cells (absorption) (Dosnon-Olette et al, 2011;Sun et al, 2012), which is higher for Fd (3.16) than Nf (2.30) (Sabljic et al, 1995). It was shown that the water solubility of chemicals, and therefore their octanol-water partition coefficient, varied differently with temperature (Shiu et al, 1997), which might explain the discrepancy in the effect of Nf and Fd at 8, 15 and 25°C in our study. Moreover, the physical properties of the membrane can also influence the translocation and distribution of toxicants having various lipophilicity (Baynes & Hodgson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] The melting points ranged from below room temperature to 485°C and included environmentally prevalent compounds such as polycyclic aromatic Table 2 depicts the observed and predicted miscibility data of 32 common organic liquids with octanol. Predicted miscibility data were obtained by use of Equation 6.…”
Section: Data Collectionmentioning
confidence: 99%
“…Table 3 depicts the melting points and the experimental and predicted molar solubilities of 123 compounds reported in literature. [6][7][8][9][10][11][12][13][14][15][16] The predicted values were obtained by use of Equation 12. Linear regression analysis was performed with SPSS Version 10.0 (SPSS Inc, Chicago, IL).…”
Section: Data Collectionmentioning
confidence: 99%